The use of communication channels in the information dissemination within the committees of Barangay Mintal government unit a case study - Remegio, Rea Gene B.
This research was conducted to examine the dissemination of information within the committees of Barangay Mintal Government Unit. It aimed to find out what communication channels the committees use in disseminating information. Moreover, it also analyzed how the committees manifested interdependence in communication using the communication channels they use. The subject of this research involved eleven committees of BMGU. Through a series of interviews and a non-participant observation, the researcher was able to gather data from these committees, the data gathered were analyzed primarily through Systems Theory. Results of this research showed that the committees of BMGU demonstrate interdependence in communication. Their interdependence is achieved through coordinating their activities and tasks using communication channels that vary in formality. The communication channels include paperwork (memoranda, committee reports), face-to-fce discussion (barangay session), and mobile phone. Paperwork is the formal communication channel used by the committees. Although the barangay session is a relatively a formal communication channel; Mobile phones are informal communication channels. Barangay sessions and mobile phones are used to reinforce decisions made through paperwork. Mobile phones supplemented the use of paperwork while barangay sessions clarified instructions. Generally, this research concluded that communication channels contribute to the interdependence of the BMGU system. The communication channels used in an organization vary in formality. Formal communication channels are used to disseminate information about routine tasks while informal communication channels are used in an non-routine tasks such as planning and decision-making. New communication technology or electronic channels are used if speed is priority. Informal communication channels discuss further what has been stated on paperwork. Thus, they supplement the use of more formal communication channels.